2021
DOI: 10.3390/ijerph18168437
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness in Occupational Groups—Trends over 20 Years and Future Forecasts

Abstract: Background: Reports have indicated a negative trend in cardiorespiratory fitness (CRF) in the general population. However, trends in relation to different occupational groups are missing. Therefore, the aim of our study was to examine the trends in CRF during the last 20 years, and to provide a prognosis of future trends in CRF, in different occupational groups of Swedish workers. Methods: Data from 516,122 health profile assessments performed between 2001 to 2020 were included. CRF was assessed as maximal oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…This can be seen as a major public health concern considering the recommendations on PA by the World Health Organization [55]. A large-scale report by Väisänen et al [56] has indicated a negative trend in cardiorespiratory fitness in the Swedish population and similar trend has also been observed in Finland [57]. Besides being a global public health concern, the lack of vigorous PA is also a special concern in the military context as, on the individual level, it may negatively affect the occupational performance, increase musculoskeletal injury risk and thus compromise overall training outcomes during service [58].…”
Section: Discussionmentioning
confidence: 99%
“…This can be seen as a major public health concern considering the recommendations on PA by the World Health Organization [55]. A large-scale report by Väisänen et al [56] has indicated a negative trend in cardiorespiratory fitness in the Swedish population and similar trend has also been observed in Finland [57]. Besides being a global public health concern, the lack of vigorous PA is also a special concern in the military context as, on the individual level, it may negatively affect the occupational performance, increase musculoskeletal injury risk and thus compromise overall training outcomes during service [58].…”
Section: Discussionmentioning
confidence: 99%
“…According to Väisänen et al [ 30 ] over the last two decades cardiorespiratory, fitness has declined in most occupational groups, particularly in blue-collar and low-skilled occupations. Consequently, procedures that encourage employees to improve good cardiorespiratory fitness, e.g., through commuting by walking or biking, climbing the stairs rather than use the elevator whenever possible might be effective approaches for improving cardiorespiratory fitness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to PA, physical fitness may also increase an individual’s capacities to cope with the demands of everyday life, including work [ 14 ]. A recent study showed that cardiorespiratory fitness (CRF) has declined in most occupational groups over the last two decades, being the greatest in blue-collar and low-skilled occupational groups [ 15 ]. CRF, especially when assessed with walking-based methods, correlates with WA [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%